2016
DOI: 10.7150/jca.15061
|View full text |Cite
|
Sign up to set email alerts
|

MiR-34a and miR-203 Inhibit Survivin Expression to Control Cell Proliferation and Survival in Human Osteosarcoma Cells

Abstract: Elevated expression of survivin is observed in a number of cancer types, including human osteosarcoma. Few studies have demonstrated that survivin expression levels can be considered an independent predictor of survival for human osteosarcoma patients. However, the underlying molecular mechanisms of survivin in the process of human osteosarcoma carcinogenesis remain unclear. In the current study, we evaluated the biological effects of survivin knockdown on osteosarcoma cell proliferation, colony formation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…According to previous reports [10][11][12], 2588 mature miRNAs have been identified in the human body, and each miRNA can widely participate in various life activities of the human body, and regulate the occurrence and development of diseases and cancers. A number of studies [13,14] showed that miR-203, miR-148b and other miRNAs were abnormally MiR-143 is located on human chromosome 5 and is downregulated in the bladder and ovarian cancer. Its expression level is significantly correlated with clinical stage, disease grade and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports [10][11][12], 2588 mature miRNAs have been identified in the human body, and each miRNA can widely participate in various life activities of the human body, and regulate the occurrence and development of diseases and cancers. A number of studies [13,14] showed that miR-203, miR-148b and other miRNAs were abnormally MiR-143 is located on human chromosome 5 and is downregulated in the bladder and ovarian cancer. Its expression level is significantly correlated with clinical stage, disease grade and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the field of osteosarcoma research, there are much more recent research confirmed that mir-34a can inhibit cell proliferation and promotes apoptosis in human osteosarcoma cells in vitro and in vivo. [21][22][23][24][25][26][27] So, we are valid to consider that mir-34a could inhibit cell proliferation and promotes apoptosis in osteosarcoma possibly. And our results strongly suggest that miR-34a was downregulated in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Naloxone can reverse this morphineinduced upregulation, proving that opioid receptors were involved in the process. Recently, it has been found that over-expressing Survivin can promote tumors to metastasize and increase genomic instability, thereby promoting tumor invasion and metastasis [39,40]. It was also shown that morphine can enhance RCC growth by promoting Survivin expression [39,40].…”
Section: Effect Of Morphine On Tumor Invasion and Metastasismentioning
confidence: 99%